THE CORRELATION BETWEEN SELF EFFICACY AND MOTIVATION LEARNING WITH MATHEMATICS LEARNING OUTCOMES STUDENTS CLASS XI IPS SMA NEGERI 5 BATAM ACADEMIC YEAR 2013/2014 - Dora Detrina Hutagalung (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2016)
This research is motivated by low self efficacy and motivation to study the effect on mathematic learning outcomes become less good. This study was carried out aimed to determine : (1) the correlation between self efficacy in mathematics learning outcomes (2) the correlation of learning motivation and learning outcomes mathematics (3) the correlation between self efficacy and motivation to learn mathematics results. This type of research is survey research with correlational approach using research subjects which its population amount to 225 students and a sample amount to 146 students. Research instrument research trials conducted on 46 respondents. Data collection of self efficacy and motivation to learn by using a questionnaire, and the learning outcomes conducted by documentation. The results of this research that there is a significant correlation between: (1) self efficacy in mathematics learning outcomes with value of  = 0,744 and  at the 5% significance level. Self efficacy contributed to 55,3% on learning outcomes of mathematics (2) motivation to learn in mathematics learning outcomes with value of = 0,579 and . Motivation to learn to contribute 33,6% of the mathematics learning outcomes (3) self efficacy and motivation to learn the mathematics learning outcomes with value of = 0,759 dan . Self efficacy and motivation to contribute 57,6% of the math learning outcomes. So it can be concluded that in this study the first hypothesis, the second and third receiving   and rejecting .   Keyword: self-efficacy, motivation, learning math